(untitled) (Research, Society and Development, 2021)
This article aims to identify the variables that can influence acts of corruption in the national scenario, based on their respective transparency indexes, considering the simultaneous performance of economic, social and legal factors, from the perspective of civil construction. The results of this research made it possible to verify which variables are statistically significant in the national corruption scenario, as well as the variables that refer to this phenomenon in the civil construction sector. The adopted methodology consists of the identification of a multiple linear regression model to evaluate and describe the relationship between the variables. For this, the data were collected on the official websites of the Federal Public Ministry, the Brazilian Chamber of the Construction Industry, the Center for Public Leadership, the Brazilian Institute of Geography and Statistics and the National Council of Justice. Then, a database was structured for the application of statistical analysis, which considered three hypotheses to be verified. The results obtained showed that, when analyzed simultaneously, the variables related to economic (GDP of Civil Construction) and social (Education Index and Per Capita Income) have statistically significant values ​​(p-value <= 0.10), while the variables associated with legal factors as influencing corruption, did not show statistical significance (p-value> 0.10). Conceptually, this study seeks to structure understandings that can assist in directing the fight against corruption in the national scenario, suggesting the formulation of public policies for areas of greater relevance.